Pengembangan Kuesioner PTFKP untuk Mengevaluasi Pelayanan Telefarmasi Berupa Kepuasan Pasien Berdasarkan Mutu Pelayanan WHO - Kusumawardani, Larasati Arrum; Puspasari, Annisa; Achmad, Reza Fadillah; Wati, Azizah (Pengurus Pusat Ikatan Apoteker Indonesia, 2024)
Telepharmacy is one of pharmaceutical service that is currently growing and widely used by community and healthcare facility in the digital era. To ensure the quality, it should meet the dimensions of healthcare service quality. According to WHO, the dimensions of healthcare service quality include effective, efficient, timely, people-centered, equitable, and safe. However, instruments to assess the quality of telepharmacy services are still very limited. This study aims to develop a PTFKP questionnaire to evaluate the quality of telepharmacy services based on WHO quality health services from the perspective of patient satisfaction. Content validation was conducted in two stages by three experts consisting of academicians and community pharmacists. Face validity, construct validity, and reliability testing were conducted on 30 respondents who met the criteria of being over 18 years old and having used telepharmacy services in the last 2 years. Content validity testing showed an I-CVI value of 0.71 (first round) and 1.00 (second round). In construct validity testing using the CITC (corrected item-total correlation) method, 10 questions did not meet the requirements initially. After revision, the r value for each question met the criteria, ranging from r= 0.378-0.857 (rtable = 0.361). Reliability testing using the internal consistency method showed a Cronbach’s alpha value of 0.805-0.900 for each dimension of service quality. The number of valid and reliable questions was 5 for each dimension of effective, efficient, people-centered, and safe, and 4 for each dimension of timely and equity. The questionnaire meets the validity and reliability requirements to be used.